2015
DOI: 10.1128/jb.02471-14
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Substrate Specificity of Two Closely Related Amino Acid Transporters, SerP1 and SerP2, of Lactococcus lactis

Abstract: The serP1 and serP2 genes found adjacently on the chromosome of Lactococcus lactis strains encode two members of the amino acid-polyamine-organocation (APC) superfamily of secondary transporters that share 61% sequence identity. SerP1 transports L-serine, L-threonine, and L-cysteine with high affinity. Affinity constants (K m ) are in the 20 to 40 M range. SerP2 is a DLalanine/DL-serine/glycine transporter. The preferred substrate appears to be DL-alanine for which the affinities were found to be 38 and 20 M f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…a and b). In control experiments, uptake by the same cells of L‐serine that is taken up by the pmf‐driven transporters SerP1 and SerP2 in L. lactis (Noens & Lolkema, ), was reduced to low levels when glucose was omitted from the assay mixture, (Fig. c) demonstrating the absence of proton motive force (pmf) in the absence of glucose.…”
Section: Resultsmentioning
confidence: 94%
“…a and b). In control experiments, uptake by the same cells of L‐serine that is taken up by the pmf‐driven transporters SerP1 and SerP2 in L. lactis (Noens & Lolkema, ), was reduced to low levels when glucose was omitted from the assay mixture, (Fig. c) demonstrating the absence of proton motive force (pmf) in the absence of glucose.…”
Section: Resultsmentioning
confidence: 94%
“…2c) might be related to a common transporter for serine and threonine. Noens & Lolkema (2014) showed that SerP1 transports L-serine, L-threonine and L-cysteine with high affinity. The decrease in L-serine consumption probably evoked the increase in L-asparagine utilization ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis, e.g., using glucose, contributes to pyruvate formation (38,39). DL-Alanine/DL-serine/glycine transporter (SerP2) imports extracellular alanine (10). ATP-driven glutamate/glutamine transporter (GlnPQ) (40) and aspartate/glutamate transporter (AcaP) import glutamate (41).…”
Section: Figmentioning
confidence: 99%
“…Thus, a sufficiently large intracellular alanine pool is vital for proper cell growth. Multiple processes in L. lactis MG1363 contribute to the pool of intracellular alanine: the uptake of oligopeptides and di-and tripeptides containing alanine residues through the Opp, Dpp, and DtpT transporters mentioned above, the further degradation by peptidases to liberate the alanine (4), the uptake of free alanine from the medium via the DL-Ala transporter SerP2 (10), and alanine synthesis from pyruvate and glutamate by the transaminase AspC (11) (Fig. 1).…”
mentioning
confidence: 99%